(untitled) (Research, Society and Development, 2022)
The Covid-19 outbreak changed the dynamic in cities around the world. To avoid the collapse in the healthcare system, several cities restricted or forbid people’s mobility to diminish the Covid-19 contagion. Meanwhile, a number of researchers developed online initiatives such as websites, apps and chatbots, to inform and guide people about the Covid-19 and its effects. In this paper, we combine data gathered from a dialogue chatbot that indicates healthcare facilities to individuals, with Covid-19 daily reports on new cases and mortality and demographic and socioeconomic factors to carry out analysis on geography and Covid-19 healthcare facilities in a major metropolitan city in Brazil. Results show that less wealthier areas are more populous, report high Covid-19 contagion level and request healthcare facilities locations more often. These findings shed light on Covid-19 healthcare facilities mobility patterns, which is influenced by area features and can be used to design and plan more equitable and accessible cities.